Empowering the community of Bokesan village through production of So Ikie (Nila-algae fish sausage) - Fransisca Shinta Maharini; Maria Amrijati Lubijarsih; Emmelia Rahmawati (Journal of Community Service and Empowerment, 2024)
Fish and algae (seaweed) are abundant commodities in Yogyakarta. The potential for high fiber sausages which have advantages needs to be socialized to the public. The aim of this activity is outreach including education and training for housewives in the hamlet of Bokesan, Sindumartani, Ngemplak, Sleman, Yogyakarta. This area already has local potential for tilapia cultivation. Housewives in Bokesan hamlet are members of the Mina Mandiri business group. The processed tilapia fish product that has been developed is tilapia fish chips or crispy tilapia. With the abundant availability of tilapia in the area, the So Ikie product (tilapia-algae fish sausage) will be developed. The Mina Mandiri business group needs insight into healthy food, So Ikie high fiber sausage products, So Ikie processing skills, packaging and labeling to increase Nutripreneurship empowerment. Nutripreneurship empowerment is carried out by providing education and training. The education provided includes material about healthy food, healthy lifestyles, and Nutripreneurship through diversification of tilapia-based preparations. The training provided is the practice of processing tilapia-algae fish sausage products as a diversification of tilapia-based products. The participants took part in community service activities with enthusiasm and enthusiasm. Empowerment of Nutripreneurship partners can be seen in increasing insight, skills, motivation and commitment to carrying out Nutripreneurship. This is demonstrated by the results of pre and posttest assessments, the quality of practical products, evaluation of activity implementation, and the implementation of follow-up programs independently by partners. The independent follow-up program implemented includes production activities resulting from training.